The role of positron emission tomography/CT in hypoxic ischaemic encephalopathy in children - Koc, Zehra Pinar; Balci, Tansel Ansal; Akarsu, Saadet; Unal, Kemal (My University, 2013)
The role of positron emission tomography/CT (PET/CT) in diagnosis and follow-up of newborns with hypoxic ischaemic encephalopathy has been documented before; however, this is the first presentation of elder children with both diagnostic and follow-up PET/CT results as far as we know. Copyright 2013 BMJ Publishing Group. All rights reserved.
Keywords: valproic acid; acute lymphoblastic leukemia; adult respiratory distress syndrome; article; artificial ventilation; basal ganglion; bradycardia; brain cortex; brain hypermetabolism; brain hypometabolism; brain metabolism; cancer chemotherapy; cancer regression; case report; child; computer assisted emission tomography; controlled study; electroencephalogram; febrile neutropenia; female; follow up; human; hypotension; hypoxic ischemic encephalopathy; male; metabolic acidosis; multiple organ failure; myoclonus seizure; neurologic examination; positron emission tomography; preschool child; priority journal; prognosis; respiratory acidosis; spasticity; unconsciousness